Screening and Determination of Potential Cellulolytic Bacteria from Mangrove Ecosystem - Batubara, Ummi Mardhiah; Suparjo, Suparjo; Maritsa, Hasna Ul; Pujianto, Eko; Herlini, Meli (Jurnal Perikanan dan Kelautan, 2022)
Mangrove ecosystem is a coastal wetland has biodiversities such as flora, fauna, and microorganisms. Microorganisms are an importants component in the mangrove ecosystem and have many roles, including source the nutrition, decomposer, and a source of biotechnology products. Cellulolytic bacteria are a group of cellulase-producing bacteria capable of breaking down cellulose into glucose monomers. This study aims to screen and determine the diversity of cellulolytic bacteria from the mangrove ecosystem. The research method has been experimental by exploring the cellulolytic bacteria in soil and sediment from the mangrove ecosystem. Three sampling locations were selected such as the litter soil, soil in the root, and soil in the tidal area. The screened of potential bacteria-producing cellulase was obtained by bacteria growth on Carboxy Methyl Cellulose (CMC) agar medium. The isolates were cultured for 48 hours at 37°C. Then, the bacteria that produced the cellulolytic activity were characterized by morphological and physiological characteristics. The results were adjusted according to Bergey's Manual of Determinative Bacteriology. The determination showed that six isolates had the same characteristics as Bacillus, Cellulomonas, Lactobacillus, and Micrococcus. The cellulolytic activity index showed that three isolates were sequentially MS06 (9,73), MS03 (6,30), and MS08 (5,41).